KEBIJAKAN PENCEGAHAN DAN PENANGANAN KEKERASAN SEKSUAL MELALUI STRATEGI DIGITAL "POJOK HUKUM" DIDESA BONGKOT KABUPATEN JOMBANG - Mochammad Fahd Akbar; Muhammad Dzikirullah H. Noho; Abdul Afif; Ahmad Faozan; Wedi Pratanto Rahayu; Ahmad Faruq (ABIDUMASY, 2026)
This community engagement program focuses on the prevention and handling of sexual violence in Bongkot Village, Jombang Regency, by strengthening the role of the Legal Awareness Group (Kadarkum) and introducing digital innovation. Referring to the legal framework of Law No. 12 of 2022 and Government Regulation No. 27 of 2024, the activities were carried out through field observation, legal counseling, interactive consultation, and case assistance. The findings reveal low legal literacy among villagers, a strong culture of taboo in reporting, and limited coordination between local actors. To address these challenges, the Pojok Hukum (Legal Corner) portal was developed as an integrated platform that provides legal education, online consultation, secure reporting, cross-institutional integration (village authorities, health centers, police, and P2TP2A), and digital campaigns. This model adopts a promotive, preventive, and responsive approach, enabling more efficient service flows, stronger victim protection, and the development of community-based legal awareness. Thus, this program underscores that villages are not merely implementers of regulations but also strategic actors in building an adaptive, participatory, and just legal ecosystem. Keywords : Sexual violence, community engagement, Law on TPKS, Government Regulation No. 27/2024, Kadarkum, legal portal, Bongkot Village